2006
DOI: 10.1111/j.1464-410x.2006.06004.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple primary malignancies in patients with renal cell carcinoma: a national population‐based cohort study

Abstract: expected number of different tumour types was calculated according to age group, gender and observation time. RESULTSOf the 1425 patients, 228 (16%) had one, 23 (1.6%) had two, three (0.2%) had three and one (0.07%) had four other primary malignancies. In all, 100 (34.8%) of the other tumours were diagnosed as antecedent, 53 (18.7%) as synchronous and 134 (46.7%) as subsequent to the RCC. Cancer in the prostate, bladder, lung, breast, colon and rectal cancer, malignant melanomas (MM) and non-Hodgkin's lymphoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
125
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(154 citation statements)
references
References 21 publications
5
125
0
6
Order By: Relevance
“…[1][2][3][4] Multiple primaries, as defined by the International Agency for Research on Cancer (IARC), are those cancers which develop in several primary sites that are not an extension, recurrence nor metastasis of each other. Multiple primaries also include tumours arising from the same site but with different morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Multiple primaries, as defined by the International Agency for Research on Cancer (IARC), are those cancers which develop in several primary sites that are not an extension, recurrence nor metastasis of each other. Multiple primaries also include tumours arising from the same site but with different morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…RCC is the most common tumor found to coexist with other malignancies [1,10,12,13,14]. In different studies the incidence of second primary malignancy associated with RCC is reported to be 12%-27.4% [1,10,11,14]. About 19% of these tumors appeared synchronously [1].…”
Section: Discussionmentioning
confidence: 99%
“…In different studies the incidence of second primary malignancy associated with RCC is reported to be 12%-27.4% [1,10,11,14]. About 19% of these tumors appeared synchronously [1]. Other primary malignant tumors most often associated with RCC are bladder, prostate, colorectal and lung cancer [1,10,12,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature reveals that renal cell carcinoma has been associated with other primary malignancies (synchronous and metachronous); like those of colon [2], rectum [2], stomach [5], prostate [2], bladder [2], endometrium [1], ovary [1], breast [2], nasopharynx [5], lung [6] and haematological malignancies.…”
Section: Discussionmentioning
confidence: 99%